Att tänka med alla sinnen: Aforismen och K. J. - Bohlin, Anna (Tidskrift för litteraturvetenskap, 2013)
Reasoning with the Senses. The Aphorism and K. J. In this article, the aphorisms of Klara Johanson (1875–1948) are related to the history of the genre. I argue that her aphorisms should be examined in the light of the romantic aphorism and be considered as a contribution to aesthetics. The etymology of the term ”aesthetics” – sensuous perception – foregrounds the body, as does the earliest uses of the term ”aphorism” (Aphorismoi was the title of Hippocrates’ famous compendium of medical propositions and recommendations). The meaning of the term was later transferred from medicine to other disciplines, most notably politics, drawing on the analogy of the relation between the health of the physical body and the health of the state (connected by the theory of the four humours). Of course, by the beginning of the 20th century, that theory was no longer valid. However, the connection between the body and the state had endured, and was now understood in terms of the romantic concept of the ”organism”. Johanson’s aphorisms unite these two aspects: the body as sensuous perception and the body related to the state. According to Gerhard Neumann’s definition, the form of the romantic aphorism is a representation of conflict between abstract, mathematical truth, and personal, sensuous truth. This conflict informs Johanson’s aphorisms, although her modern take on the romantic conflict was more in line with the Italian philosopher Benedetto Croce, whose works Johanson introduced and translated into Swedish. In his view, aesthetics should precede logic, since individual perception precedes any understanding of a pure concept. I argue that Johanson’s aphorisms constitute a political statement, situating the individual truth at the centre of experience, and defending the need to take personal differences into account in order to heal the social ”organism” of society. To think with all your senses is to accrue historical knowledge; an aesthetic method with political implications.